2015
DOI: 10.3390/ijms160511417
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Candidate Genes Associated with Defense Responses to Phytophthora capsici in Pepper Line “PI 201234”

Abstract: Phytophthora capsici (Leonian), classified as an oomycete, seriously threatens the production of pepper (Capsicum annuum). Current understanding of the defense responses in pepper to P. capsici is limited. In this study, RNA-sequencing analysis was utilized to identify differentially expressed genes in the resistant line “PI 201234”, with 1220 differentially expressed genes detected. Of those genes, 480 were up-regulated and 740 were down-regulated, with 211 candidate genes found to be involved in defense resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…8). However, the magnitude of the fold changes varied between RNA-seq and qRT-PCR experiments, and this phenomenon also appeared in several previous studies (Cao et al, 2018;Dong et al, 2017b;Wang et al, 2015;Zhang et al, 2018b). This may be due to sample collection for previous RNAseq and qPCR experiments at different times, or differences in RNA extraction or cDNA synthesis.…”
Section: Discussionsupporting
confidence: 52%
“…8). However, the magnitude of the fold changes varied between RNA-seq and qRT-PCR experiments, and this phenomenon also appeared in several previous studies (Cao et al, 2018;Dong et al, 2017b;Wang et al, 2015;Zhang et al, 2018b). This may be due to sample collection for previous RNAseq and qPCR experiments at different times, or differences in RNA extraction or cDNA synthesis.…”
Section: Discussionsupporting
confidence: 52%
“…Recent studies have indicated that a novel peroxidase ( CanPOD ) and oxysterol-binding protein ( CanOBP ) genes, which are involved in the defense response to P. capsici infection, exhibit expression patterns similar to these CaSBP s ( Liu, 2009 ; Wang et al, 2013b ). Moreover, similar expression patterns are also found in some defense-related genes – such as the disease-associated protein gene ( CABPR1 ), β-1,3-glucanase gene ( CABGLU ), and peroxidase gene (CAPO1 ) – in pepper roots after inoculation with compatible and incompatible P. capsici ( Wang, 2013 ). However, according to Kim and Hwang (2000) , the expression of CABPR1 is higher in the compatible interaction than in the incompatible interaction.…”
Section: Discussionmentioning
confidence: 72%
“…As Figure 3, Figure 6, and Figure 7 showed, CaSBP12 plays a negative regulatory role in the process of P. capsici infection. Therefore, the disease index percent was also calculated after inoculation with the HX-9 strain using the root-drench method as described by Wang (2013) [20]. After inoculation with the HX-9 strain, the infection was monitored at day 16.…”
Section: Resultsmentioning
confidence: 99%
“…Zoospore concentration was counted and adjusted to 1 × 10 5 cfu/mL using the method described by Jin et al (2016) [1]. Then, 5 mL of this zoospore was used to inoculate the CaSBP12 -silenced and control pepper plants using the root-drench method as described by Wang (2013) [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation